Provocations of Virtue : Rhetoric, Ethics, and the Teaching of Writing - Duffy, John, 1955- (Book collections on Project MUSE., 2019)
"Explores the role of writing teachers in counteracting the polarized "post-truth" of public argument. Writing teachers are uniquely positioned to address the crisis of public discourse because their work is tied to ethical language practices known to philosophers as "the virtues"--Truthfulness, accountability, open-mindedness, and intellectual courage"--Provided by publisher